Satysfakcja klienta wewnętrznego w świetle badań na przykładzie Miejskiego Przedsiębiorstwa Wodociągów i Kanalizacji Sp. z o.o. w Lesznie - Miedziarek, Sławomir; Sutersk, Heronim (Searching for Perfection by Means of Questionnaire Research for the Internal Client of a Chosen Organization, 2008)
The paper is an attempt to identify the fulfillment of the needs of blue collar workers. There has been done the appreciation of the most important factors for the participants of the questionnaire. The research and the results have been based on the proper analysis. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 494-505